Structure-based design of Trifarotene (CD5789), a potent and selective RARγ agonist for the treatment of acne. Issue 10 (1st June 2018) - Thoreau, Etienne; Arlabosse, Jean-Marie; Bouix-Peter, Claire; Chambon, Sandrine; Chantalat, Laurent; Daver, Sébastien; Dumais, Laurence; Duvert, Gwenaëlle; Feret, Angélique; Ouvry, Gilles; Pascau, Jonathan; Raffin, Catherine; et al.
Graphical abstract: Highlights: X-ray of known RARγ-agonist CD437- RARγ complex was obtained. Hypothesis for the isotype selectivity of known RARγ-agonist CD437 are presented. Knowledge derived from the CD437- RARγ complex was used on a novel series of agonists. Optimisation of potency, selectivity and metabolism led to the identification of CD5789. CD5789, a potent and selective γ-selective RAR agonist is in Phase 3 clinical trials for the topical treatment of acne. Abstract: Retinoids have a dominant role in topical acne therapy and to date, only RARβ and RARγ dual agonists have reached the market. Given the tissue distribution of RAR isoforms, it was hypothesized that developing RARγ -selective agonists could yield a new generation of topical acne treatments that would increase safety margins while maintaining the robust efficacy of previous drugs. Structural knowledge derived from the X-ray structure of known γ-selective CD437, suggested the design of a novel triaryl series of agonists which was optimized and ultimately led to the discovery of Trifarotene/CD5789.